소아의 천공성 충수염에 시행한 개복 충수절제술과 복강경 충수절제술의 비교 - 남소현(So-Hyun Nam); 김대연(Dae-Yeon Kim); 김성철(Seong-Chul Kim); 김인구(In-Koo Kim) (Annals of surgical treatment and research, 2009)
Purpose: It is controversial to do laparoscopic appendectomy in children with perforated appendicitis. Recently, we have adopted laparoscopic appendectomy as a first-choice method in children with perforated appendicitis. We investigate the results of laparoscopic appendectomy in perforated appendicitis and compare it with open technique. Methods: We studied retrospectively the patients who underwent the appendectomy by either a laparoscopic or open technique for perforated appendicitis between January 2001 and December 2005. There were 117 patients in the open appendectomy (OA) group and 45 patients in the laparoscopic (LA) group. Results: The operation times were significantly longer for the LA group than for the OA group (OA group 76.3±23.7 vs. LA group 95.4±32.4 min) (P＜0.05). The hospital days were also longer in the LA group than the OA group (OA group 8.7±4.4 vs. LA group 11.0±6.3 (days)). However, there was no difference in time to diet (OA group: 5.0±3.3 vs. LA group: 5.4±2.9 (days)) (P＞0.05) and in the rate of complications (OA group: 36/117 vs. LA group: 13/45) (P＞0.05) between the two groups. The incidence of postoperative ileus, intraabdominal abscess and wound infection was lower in LA group, but not significantly. Conclusion: Operation times and hospital days were longer in the LA group. But the incidence of complication was similar between the two groups. Considering little postoperative scar and less pain, laparoscopic appendectomy could be regarded as the optimal surgical therapy in children with perforated appendicitis. KCI Citation Count: 3